A case study of learning styles among top students in Universiti Malaysia Sabah - Alfred Chan Huan Zhi; Muhammad Idris Bullare @ Bahari; Lailawati Madlan @ Endalan; Siti Rafidah Md Said; Darwis Manainus Awang Kangit (Georgian Technical University, 2023)
This paper looks at the top students final year in their program for the last semester from the Faculty of Psychology and Education, Universiti Malaysia Sabah. There were seven-programme offered in the Faculty of Psychology and Education which is seven top students were served as a subject in this study. We present an exploratory multiple case studies of comprehending and categorising the learning styles of top students. The purposed of this study was conducted to find out and specify their learning and studying style that allowed them to achieve the high rank in their program. This research was used a rigorous multi-step approach for its qualitative methodology. In order to find out the top students’ Universiti Malaysia Sabah learning style were preferred more than 10’s learning styles model was used. As a base line in this research, there are six themes were used in this case studies, which is T1- Lecture, T2- Tutorial, T3- Individual Assignment, T4- Group Assignment, T5- Study Tactic and T6- Lecturer. Results indicated that the six themes of learning style preferences considered in the interview questions were positively preferred.